2018
DOI: 10.4236/jep.2018.94026
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability and Radiative Impact of Aerosol along the Brahmaputra River Valley in India: Results from a Campaign

Abstract: The first ever land campaign to study the spatial variability of the aerosol characteristics along the Brahmaputra river valley (BRV) in Assam, North-Eastern India, was conducted during 2011. Measurements were made over 13 locations for Aerosol Optical Depth (AOD), scattering coefficient, particulate matter, black carbon (BC) concentration and meteorological parameters. The BRV is divided into three sectors longitudinally viz western sector (WS), central sector (CS), and eastern sector (ES). Significant Spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
2
7
0
Order By: Relevance
“…The study region is chosen because it is of genuine research importance due to the simultaneous existence of a range of both natural and anthropogenic aerosols (e.g., sand dust, marine, forest re, industrial emission, etc.,) as reported in earlier works (Pathak et al 2015; Kundu et al 2018; Barman et al 2018; 2019) that makes the region hotspot for aerosol research. The station witnessed high precipitation throughout the monsoon every year and a larger water body nearby, causing a greater rate of evaporation/condensation over the study area.…”
Section: Introductionsupporting
confidence: 67%
“…The study region is chosen because it is of genuine research importance due to the simultaneous existence of a range of both natural and anthropogenic aerosols (e.g., sand dust, marine, forest re, industrial emission, etc.,) as reported in earlier works (Pathak et al 2015; Kundu et al 2018; Barman et al 2018; 2019) that makes the region hotspot for aerosol research. The station witnessed high precipitation throughout the monsoon every year and a larger water body nearby, causing a greater rate of evaporation/condensation over the study area.…”
Section: Introductionsupporting
confidence: 67%
“…Production of high absorbing aerosol (BC) over different parts of Assam during the winter season has been reported by Kundu et al ( 2018 ), due to rice crop residue burning, small-scale forest fires, shrubs etc. Transportation of aerosol from IGP by strong westerly wind also contributes to high BC concentrations during the January and February months.…”
Section: Resultsmentioning
confidence: 97%
“…BC also rises simultaneously. Cluster analysis of seasonal wind back trajectories showed that the majority of them are passed through the IGP and Bangladesh region, which is relatively polluted from industrial emissions, brick kiln releases, burning of fossil fuels, firewood, and cow dung burning and stubble (Barman et al, 2018 ; Kundu et al, 2018 ; Pathak et al, 2015 ). As evident by seasonal mean trajectories, gaseous pollutants, including BC, are being imported by the winds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Model-model comparisons have shown that different radiative transfer codes may agree well if they are run with identical optical properties as input (Halthore et al, 2005). The SBDART model is selected here by its high accuracy (Li et al, 2010), besides it has been consistently developed over the past few decades (Kundu et al, 2018) and has been extensively applied to ARF in studies of atmosphere energy budget and also in satellite remote sensing (Luo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%